Modeling of Damage Evaluation and Failure of Laminated Composite Materials - Joy Mathavan, J.; Hafiz Hassan, M.; Gérald, F. (Springer Nature, 2023)
Due to the anisotropy and heterogeneity of fiber-reinforced composite materials, the growth of damage in the composite materials is a complicated process. In contrast to metallic materials, damage to fiber-reinforced composites under static or cyclic loading situations [1] with very large amplitudes is dispersed rather than confined [2]. The damage-accumulation process, which is associated with the beginning and progression of a damage, frequently causes composite materials to lose some of their elastic properties, known as stiffness degradation. In reality, the change in stiffness during the fatigue life of a fibre composite material caused by change in residual strength is normally lesser than the degradation [3]. Additionally, since the development of microdefects always occurs before the formation of macrocracks, the spread of a single macrocrack in the structure does not always cause for the failure in a composite [4]. Various microdamage mechanisms begun based on the level of anisotropy, inhomogeneity, and the loading conditions used. They can manifest and grow individually or in combination, resulting in a range of situations for the failure of composite materials or for the degradation of their properties [5].Additionally, the causes of failure of composite materials and degradation of properties are dependent on the scaling factors of the composite structure. As a result, multiscale modelling of the damage accumulation process in relation to the deterioration of the property is required [6, 7].